Bibliometric Analysis: Development of Electronic Teaching Materials for Physics Laboratory Courses to Train Scientific Creativity of Prospective Physics Teachers - Muhammad, Nurlaela; Taib, Suryani; Misbah, Misbah; Zulfah, Raihanah (Kasuari: Physics Education Journal (KPEJ), 2023)
The development of electronic teaching materials continues to be carried out, so that there are many articles that examine this matter. Comprehensive information regarding its development is carried out by reviewing electronic teaching materials research documents using bibliometric analysis. Data mining was carried out on May 1, 2023 by searching the Scopus database using the keywords "electronic AND teaching AND materials" OR "electronic AND learning AND materials with the term "science AND education" OR "science AND learning". The software used are VOSviewer and Microsoft Office Excel. Based on the results of data analysis, it was found that the authors with the most citations were Al-Azzam, N.; Elsalem, L.; Friday, A.A.; Obeidat, N. One of the most productive affiliates is Jordan University of Science and Technology, which comes from the most productive country, namely the United States. In addition, the most productive publication is BMC Medical Education with Q1 category. Trends in the development of electronic teaching materials are associated with Covid-19, social media, games, major clinical studies, software, adults, problem solving, PBL in 2020 – now.